2019
DOI: 10.7241/ourd.20194.1
|View full text |Cite
|
Sign up to set email alerts
|

Nail alterations in patients affected by endemic pemphigus foliaceus in el Bagre, Colombia

Abstract: Background: We have characterized a new variant of endemic pemphigus foliaceus in El Bagre (El Bagre-EPF) (AKA pemphigus Abreu-Manu) and surrounding municipalities. Herein, we describe nail alterations in several patients affected by this disease. In the pre-steroid era, patients with endemic pemphigus foliaceus (EPF), especially in Brazil where the disease is known as fogo selvagem (FS), were described to have some nails changes including the Viera's sign (yellowish of the nail). In this study, we have attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…As other studies have shown, nail involvement is taken as an indicator of the severity of the pemphigus [8,9]. Laffitte, et al, suggested that expression of Dsg1 and Dsg3 in the periungual skin is disease-specific, and autoantibodies against Dsg3 alone may have a role in the development of paronychia in PV which explains why paronychia is the most frequent nail involvement in pemphigus vulgaris [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have shown, nail involvement is taken as an indicator of the severity of the pemphigus [8,9]. Laffitte, et al, suggested that expression of Dsg1 and Dsg3 in the periungual skin is disease-specific, and autoantibodies against Dsg3 alone may have a role in the development of paronychia in PV which explains why paronychia is the most frequent nail involvement in pemphigus vulgaris [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this sign remains unknown. [ 17 ] Virchow's sign : The father of modern pathology “Rudolf Carl Virchow” (1821–1902) observed that the tongue often showed a smooth base in congenital syphilis. This is called Virchow's sign.…”
Section: Introductionmentioning
confidence: 99%